Can difficult intubation be accurately predicted using upper lip bite test? - Shah, Azmat Ali; Rafique, Khalid; Islam, Mujahid (Journal of Postgraduate Medical Institute, 2014)
Objective: To determine the diagnostic accuracy of Upper Lip Bite Test (ULBT) in the diagnosis of difficult intubation taking Cormack-Lehane's classification as the gold standard. Methodology: This cross-sectional validation study was carried out at Ayub Teaching Hospital, Abbotabad Hospital from February to December 2012. 450 patients aged â‰¥16 yr, scheduled to undergo surgery under general anesthesia were included in the study. Preoperatively, two anesthesiologists not involved in intubating the airways of the patients evaluated the patients using ULBT. Anesthesiologists, who were not informed of the preoperative upper lip bite classes, assessed difficulty of laryngoscopy at intubation according to the method described by Cormack and Lehane. The preoperative assessment data and the intubation findings were used to determine the accuracy of the above mentioned tests in predicting difficult intubation. Accuracy, Sensitivity, specificity, accuracy, and positive and negative predictive values were calculated for ULBT. Results: The mean age of the patients was 38.8±14.09 years and 196 (43.6%) were males. Forty seven (10.4%) of them were found at laryngoscopy to have airways that were difficult to intubate, exhibiting laryngoscopy grade III or IV. There were no failed intubations. The calculated accuracy, sensitivity, specificity, positive predictive value and negative predictive value of ULBT were 95.5%, 91.5%, 96%, 72.8% and 98.9% respectively. Conclusion: ULBT is a highly accurate, sensitive and specific for predicting difficult intubations.